Understanding the obstacles (financial and non financial) faced by the women entrepreneurs in the fashion sector in India - khandelwal, pallavi (2009)
Women entrepreneurs continue to become the center of attention of several researches since entrepreneurial activity amongst women has risen greatly over the last few years. However, despite apparent gains, women seem to face a host of barriers that forces them to lag behind their male counterparts in every country, especially a developing country like India. This paper will review the literature on entrepreneurship, female entrepreneurship and its scope in India, mainly focusing on the Indian fashion industry. The paper then discusses barriers women entrepreneurs’ face, which will be divided mainly into three themes, family and society related barriers, financial barriers and industry related barriers. The study was conducted in two stages with the help of qualitative research methods i.e. questionnaires and in-depth interviews with nine women entrepreneurs residing in the capital city, New Delhi. By examining these subjects together, the research will be able to highlight the inability of the Indian fashion industry in taking an international stand. Lastly, bringing together the theoretical and practical findings, the final conclusion of the research will be discussed with its limitations and further areas of research.